Core microbe Bifidobacterium in the hindgut of calves improves the growth phenotype of young hosts by regulating microbial functions and host metabolism - Yimin Zhuang; Duo Gao; Wen Jiang; Yiming Xu; Guanglei Liu; Guobin Hou; Tianyu Chen; Shangru Li; Siyuan Zhang; Shuai Liu; Jingjun Wang; Jianxin Xiao; et al. (Microbiome)
Abstract Background The growth and health of young ruminants are regulated by their gut microbiome, which can have lifelong consequences. Compared with subjective grouping, phenotypic clustering might be a more comprehensive approach to revealing the relationship between calf growth state and core gut microbes. However, the identification of beneficial gut bacteria and its internal mechanisms of shaping host phenotype differentiation remains unclear. Results In this study, calves were divided into two clusters, cluster1 and cluster2, based on 29 phenotypic indicators using cluster analysis. Calves in cluster2 showed better growth performance, including higher body weight (BW), average daily gain (ADG), and dry matter intake (DMI), as well as better serum indicators with a high level of total superoxide dismutase (T-SOD), interleukin-6 (IL-6), and insulin-like growth factor-1 (IGF-1) compared to those in cluster1. Multi-omics was used to detect microbial features among calves in different phenotypic clusters. Distinct differences were observed between the two clustered gut microbiomes, including microbial diversity and composition. The close relationships between growth performance, blood metabolites, and microbiome were also confirmed. In cluster2, Bifidobacterium members were the dominant contributors to microbial metabolic functions with a higher abundance. Furthermore, pathways involved in carbohydrate degradation, glycolysis, and biosynthesis of propionate and proteins were active, while methane production was inhibited. In addition, the diversity and richness of hindgut resistome in cluster2 were lower than those in cluster1. The isolation and culture of Bifidobacterium strain, as well as the mice experiment, indicated that B. longum 1109 from calf feces in cluster2 could promote the growth of young hosts, enhance their blood immunity and antioxidation, and improve the development of hindgut. Conclusions In summary, cluster analysis has proved to be a feasible and reliable approach for identifying phenotypic subgroups of calves, prompting further exploration of host-microbiome interactions. Bifidobacterium as a core microbe in the hindgut of calves may play a crucial probiotic role in host phenotypic differentiation. This study enhances our comprehension of how gut core microbe shapes the host phenotype and provides new insights into the manipulation of beneficial gut colonizers to improve the growth performance and productivity of young ruminants. Video Abstract